(3JMbjb eSFdI hdGjI GdhUi Ydi fcGM GdUZjQjfs - (3GHf YHO Gddg eMeO LYaQ GdMhjRGhj GdceQj GdGUagGfjs
(3ChdgG (B:s
(3GdMeO ddg GdHGbi hMOg HEjVGM Ldjg GdMGd ai hdGjI GdehUi Ydi fcGM GdUZjQjf djQJaY GdNdGa Hjf GdaQjbjf s
(3BNQgG (B:s
(3ai NUhU gPg GdeSFdI ai GdOOhS hgPg YHGQJg hgPg YHGQJg hjbHd bhdg ai GdEfaGb Ydi GdWad heGdg HGdeYQha GfJgi gPG BNQ cdGe eDda GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B12s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdeLGejYs